PENGARUH PERPUTARAN MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS DAN HARGA SAHAM - Hamdi, Ali (Department of Management, 2013)
Ali HamdiPT. Graha Sekar Kencana SurabayaE-mail: ali_hamdii@yahoo.co.idABSTRACTThe research aim to examine (1) whether the cash, receivables, inventories turnover, current ratio,acid test ratio and cash ratio simultaneously and partially affect the NPM, ROA, ROE and stockprice, (2) whether those variables also positively and significantly effect on stock prices through theNPM, ROA and ROE. This study used the secondary data which taken from BEI at MuhammadiyahUniversity of Malang. The number of companies were only 7 in 2008 to 2011 and listed at the StockExchange. The sampling was total sampling. Analysis techniques used path analysis. The resultsshowed that the cash, receivables, inventories turnover, current ratio, acid test ratio and cash ratiowere not significant simultaneously effect on NPM but positive and significant effect on ROA andROE. Whereas ROA and ROE positive and significantly effect on stock prices. Partially, cash, receivablesturnover and acid test ratio were not significant and negative effect on NPM. Inventory turnover,current ratio and cash ratio were not positive effect. Cash, receivables and inventories turnoverwere not significant and negative effect to ROA whereas current ratio, acid test ratio and cash ratiowere either. Cash, receivables turnover and acid test ratio were not significant negative effect onstock prices through the NPM, ROA and ROE.Keywords: Cash turnover, receivables turnover, inventories turnover, NPM, ROA and ROE.